2018
DOI: 10.1075/itl.00005.nat
|View full text |Cite
|
Sign up to set email alerts
|

Reading a whole book to learn vocabulary

Abstract: This paper investigates whether it is a good idea to choose a book that interests you and read it through from the beginning to the end learning all the new words you meet. For the analysis, it is assumed that learners already know the most frequent 3,000 words of English. The criteria used to guide this investigation include the number of unknown words met, the usefulness of the unknown words, the density of the unknown words, and the number of repetitions of the unknown words. Reading a whole book intensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Repeated encounters with a word during reading or through gap-fill tasks enhance learners’ attention and retrieval of learned information about the word from previous encounters. The ILH exclusively centers on the process of learning unknown words, neglecting to incorporate retrieval opportunity as a crucial component (Laufer, 2020); however, including it as a variable enhances the ability to predict incidental vocabulary acquisition (Nation & Webb, 2011). The frequency of exposure to target words seems to be the crucial factor for acquisition (Folse, 2006; Yanagisawa & Webb, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated encounters with a word during reading or through gap-fill tasks enhance learners’ attention and retrieval of learned information about the word from previous encounters. The ILH exclusively centers on the process of learning unknown words, neglecting to incorporate retrieval opportunity as a crucial component (Laufer, 2020); however, including it as a variable enhances the ability to predict incidental vocabulary acquisition (Nation & Webb, 2011). The frequency of exposure to target words seems to be the crucial factor for acquisition (Folse, 2006; Yanagisawa & Webb, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, three groups of students were allocated varying amounts of time to complete their respective tasks: 40 to 45 min for the reading comprehension task, 50 to 55 min for the reading and gap-fill task, and 70 to 80 min for the reading and composition task. Therefore, the observed superior outcomes associated with the composition task may be a result of the greater amount of time allocated to this task, rather than solely the inherent effectiveness of the IL associated with it (Hazrat & Read, 2022; Nation & Webb, 2011). It is worth noting that positive correlations were found between time on task and learning gains (Huang et al, 2013; Yanagisawa & Webb, 2021), as well as between the IL and time on task (Yanagisawa & Webb, 2021), suggesting that tasks with higher ILs generally require more time for completion, leading to improved vocabulary gains.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies from the last decade have shown a positive relationship between reading and vocabulary knowledge (e.g., González-Fernández & Schmitt, 2015;Peters, 2018;Schmitt & Redwood, 2011); it has to be noted, though, that all these studies have been conducted on university students. Many of the studies focusing on reading as a source for incidental vocabulary development have used a definition where reading equals reading printed materials: books, newspapers, magazines (e.g., Nation, 2018). An association with exposure to printed books is the number of books in the home, often used in international large-scale studies such as PISA as an index of socio-economic status, which may exert a considerable influence on academic achievement (Evans, Kelley & Sikora, 2014).…”
Section: Extramural Englishmentioning
confidence: 99%
“…("大家 可以学老师读,没有什么压力"). The use of reading materials that match the ability of learners and with recurring vocabulary and structures, such as graded readers, can support their reading (Day, 2018;Hill, 2001;Nation, 2018). Additionally, it is also documented that pupils can benefit from having assistance from an adult or teacher-directed instruction to guide them in learning materials that are slightly above their current ability (Namaziandost et al, 2019;Young et al, 2015).…”
Section: Group Interview With the Participantsmentioning
confidence: 99%